Legal Education and Training in Kenya: Challenges and Prospects - Ratemo Tom Junior (Journal of Indonesian Constitutional Law, 2025)
The legal profession has attracted and continues to attract numerous high school and college graduates who aspire to join the profession. This is primarily due to various reasons, which, among other things, relate to the fact that it is one of the courses that offers a multitude of career options, job security, respect, and financial stability. Despite the foregoing, the profession faces myriad challenges. For instance, high standards are set to excel in the profession and/or to accredit legal education service providers. Excessive competition among law schools for the dwindling pool of qualified prospective students, combined with inadequate funding, has adverse effects on staff recruitment, research, and institutional development. It is for these reasons that this paper, employing a doctrinal research method, endeavors to analyze the history of legal education and training, as well as the regulatory framework that facilitates it in Kenya, with a specific emphasis on the Bachelor of Laws and Advocates Training Programmes. Additionally, the paper examines the role, challenges, and prospects of the Council of Legal Education and the Commission for University Education in regulating and supervising legal education in Kenya, with a particular focus on promoting quality in legal education. Finally, in order to enhance quality in legal education in Kenya, the paper proposes two main recommendations: amendment of the Kenya School of Law Act 2012 and the Legal Education Act 2012 to cure the existing superiority contest between the Acts and designing law programmes taking into account the current and future market demands.